2022
DOI: 10.1161/jaha.121.024848
|View full text |Cite
|
Sign up to set email alerts
|

Valve‐in‐Valve Transcatheter Aortic Valve Replacement Versus Redo Surgical Aortic Valve Replacement for Failed Surgical Aortic Bioprostheses: A Systematic Review and Meta‐Analysis

Abstract: Background In the absence of randomized controlled trials, reports from nonrandomized studies comparing valve‐in‐valve implantation (ViV) to redo surgical aortic valve replacement (rAVR) have shown inconsistent results. Methods and Results PubMed/MEDLINE, Google Scholar, and CENTRAL (Cochrane Central Register of Controlled Trials) were searched through December 2021. Meta‐Analysis of Observational Studies in Epidemiology guidelines were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
(59 reference statements)
0
13
0
1
Order By: Relevance
“…Although there are no RCTs examining the long-term outcomes of ViV TAVR versus redo-SAVR, several meta-analyses of observational studies have been conducted to compare the short- and long-term outcomes of these procedures. Many of these studies demonstrated a reduction in 30-day mortality in patients who undergo ViV TAVR compared to redo-SAVR, but data regarding long-term mortality outcomes remain limited [ 11 , 37 , 38 , 39 , 40 , 41 ]. In one meta-analysis, 12 studies were included to compare the results of ViV TAVR to redo-SAVR procedures in patients with failed THVs or surgical bioprosthetic valves [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although there are no RCTs examining the long-term outcomes of ViV TAVR versus redo-SAVR, several meta-analyses of observational studies have been conducted to compare the short- and long-term outcomes of these procedures. Many of these studies demonstrated a reduction in 30-day mortality in patients who undergo ViV TAVR compared to redo-SAVR, but data regarding long-term mortality outcomes remain limited [ 11 , 37 , 38 , 39 , 40 , 41 ]. In one meta-analysis, 12 studies were included to compare the results of ViV TAVR to redo-SAVR procedures in patients with failed THVs or surgical bioprosthetic valves [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study showed no significant difference in the incidence of stroke, acute renal dysfunction, or need for permanent pacemaker placement between both groups [ 38 ]. Another meta-analysis of 15 observational studies found reduced 30-day mortality and acute kidney injury in ViV TAVR patients compared to SAVR patients (2.8% vs. 5.0%, p = 0.02) [ 40 ]. This study found that midterm mortality (1–2 years post-procedure) was similar between the two groups, but the incidence of severe PPM, prosthetic aortic regurgitation, and mean transvalvular gradient was higher in the ViV TAVR group [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is our opinion that the highest-risk procedure should be performed first while the patients are still young to minimize the need for surgical interventions in older and higher-risk patients in the future [38]. Careful evaluation and planning on the order and sequence of treatment options is essential (Figure 2) [39][40][41][42]. Recent data on reoperations and the valve explanation following TAVR highlight the significant surgical risks involved [43,44].…”
Section: Lifetime Managementmentioning
confidence: 99%